Explanation of difenoconazole removal by chitosan with Langmuir adsorption isotherm and kinetic modeling - Altun, Şükran; Kadak, Ali Eslem; Küçükgülmez, Aygül; Gülnaz, Osman; Çelik, Mehmet (Springer Science and Business Media LLC, 2022)
In this study, the adsorption of toxic difenoconazole pesticide was investigated by using chitosan. In the first phase of the study, chitosan was extracted from deep-water pink shrimp (Parapenaeus longirostris) shells, by deacetylation of the chitin, which is separated and disposed of after meat extraction in processing facilities in Turkey. The deacetylation degree, molecular weight, viscosity, moisture, and crude-ash values of the extracted chitosan were determined. Chitosan, having a high deacetylation degree (90.21%), was used as the adsorbent. In the second phase of the study, the effects of pH, temperature, and pesticide concentration on the adsorption were investigated. The optimum pH level for pesticide adsorption was determined as 5. It was observed that the adsorption increases as the temperature increases. A rapid increase was observed within the first 5 min of the 60-minute adsorption process in difenoconazole concentrations of 5, 15, and 25 µg/L, and after 10 min, the adsorption rate was stable. The Langmuir isotherm parameters regarding the adsorption were determined as aL = 0.635, kL = 15.10, and the Qmax value was calculated as 23.77 mg/g. In the evaluation of overall study results, it was determined that the chitosan biopolymer is a suitable adsorbent for difenoconazole pesticide adsorption.